Psychological characteristics of the national Hungarian table tennis team - Trpkovici, M.; Pálvölgyi, A.; Ács, P. (Proceedings Book of The 16th ITTF Sports Science Congress Budapest (HUN), April 19th - 20th, 2019, 2020)
Aim: The aim of the study was to investigate the relationship between age category, assertiveness, temperament and character dimensions and the playing styles of the players. Method: A total of 32 table tennis players from the Hungarian national team were tested (average age 19,31, male=7, female=25). Three questionnaires were used. (1) Competitive State Anxiety Inventory-2 (CSAI-2) with 3 subscales (cognitive and somatic anxiety, and self-confidence); (2) Assertiveness Questionnaire (AST) with 2 subscales (offensive, defensive); (3) Temperament and Character Inventory (TCI) with 7 subscales, out of these 4 temperament subscales (novelty seeking, harm avoidance, reward dependence, persistence) and 3 character subscales (self-directedness, cooperativeness, self-transcendence). Results: We used SPSS 22 and found positive relationship between assertiveness and attacking playing style (p=0,02). Significant difference were found between gender in cognitive (p=0,01) and somatic anxiety (p=0,01). Among age categories (cadet, junior, adult) the only positive relationship were found between the offensive subscale of assertiveness and junior category (p=0,02). There were no significant difference between the temperament and character dimensions and age categories, playing styles and assertiveness. Conclusion: Results showed that assertiveness can be a core element of the attacking style.